Through the untamed sky - Alvarez, Jennifer Lynn (Alvarez, Jennifer Lynn. Riders of the Realm, 2019)
Even though neither Rahkki nor Echofrost want to be paired as a rider and flier, they must work together to fly with the Sky Guard, free the wild herd of winged horses from the giants, and stop a plot to dethrone the queen.